PENGOPTIMALAN KEMAMPUAN MAHASISWA DALAM MATA KULIAH LINGUISTIK UMUM MELALUI PROGRAM ASESMEN DAN TUTORIAL AKADEMIK MAHASISWA - Mardikantoro, Hari Bakti (Lembaran Ilmu Kependidikan, 2009)
General Linguitics subject is a fundamental subject offered to semester 1students hoping to be the foundation for the students to understand other linhuisticsubjects. However, the studentsÃ¢â¬â¢ achievement in the subject was not yet optimum. Thesubject of the study was 400 freshmen of Indonesian language and literature studyprogram of Indonesian Language and Literature Department of Semarang StateUniversity who took general linguistic class. The study applied classroom actionresearch with two cycles. The results of the research were that the assessment andacademic tutorial for students in general linguistic could improve the studentsÃ¢â¬â¢ gradeand knowledge. This was shown from the improvement of the the pretest, formativetest, and posttest at the end of cycles 1 and II. The sum of the score of the pretest,formative test, and posttest at the end of cycle I are subsequently 1810, 2875, and2981. The average score of the three assements improved from 50.3 to 71.9 and 74.5.At the end of the cycle II the score improved from 3196 to 3384 with the averagescore improving from 81.7 to 84.6. Besides, the assessment and student academictutorial could change the behavior of the students who attended general linguisticclass. This was seen from the more positive change of the studentsÃ¢â¬â¢ behavior. With theplanned activities and obtained result, the writer suggests/recommends that thisactivity is applied to other subjects.Kata kunci : asesmen, tutorial, linguistik umum